Predictive values of the postoperative neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio for the diagnosis of early periprosthetic joint infections: a preliminary study - Guanglei Zhao; Jie Chen; Jin Wang; Siqun Wang; Jun Xia; Yibing Wei; Jianguo Wu; Gangyong Huang; Feiyan Chen; Jingsheng Shi; Jinyang Lyu; Changquan Liu; et al. (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Several studies have been conducted to report diagnostic values of the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) in the many diseases, such as oncological, inflammatory, and some infectious diseases. However, the predictive value of these laboratory parameters for early periprosthetic joint infections (PJIs) has not yet been reported. The aim of this study was to determine predictive values of the postoperative NLR, PLR, and LMR for the diagnosis of PJIs. Methods In this retrospective study, 104 patients (26 early PJI cases and 78 non-PJI cases) who underwent total joint arthroplasty were enrolled in this study. All the patients were then categorized into two groups: PJI group, patients with the diagnosis of PJI (26 patients; 14 males, 12 females; mean age = 65.47 ± 10.23 age range = 51–81 ) and non-PJI group, patients without PJI (78 patients; 40 males, 38 females; mean age = 62.15 ± 9.33, age range = 41–92). We defined “suspected time” as the time that any abnormal symptoms or signs occurred, including fever, local swelling, or redness around the surgical site between 2 and 4 weeks after surgery and before the diagnosis. Suspected time and laboratory parameters, including NLR, PLR, LMR, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP), were compared between both groups. The trends of postoperative NLR, LMR, PLR, CRP, and ESR were also reviewed. The predictive ability of these parameters at the suspected time for early PJI was evaluated by multivariate analysis and receiver operating characteristic (ROC) curve analysis. Results NLR, PLR, and LMR returned to preoperative levels within 2 weeks after surgery in the two groups. In the PJI group, NLR and PLR were significantly increased during the incubation period of infection or infection, and LMR was significantly reduced, although 61.5% (16/26) of the patients had normal white blood cells. Interestingly, ESR and CRP were still relatively high 2 weeks after surgery and were not different between the two groups before infection started (p = 0.12 and 0.4, respectively). NLR and PLR were significantly correlated with early PJI (Odds ratios for NLR and PLR = 88.36 and 1.12, respectively; p values for NLR and PLR = 0.005 and 0.01, respectively). NLR had great predictive ability for the diagnosis of early PJI, with a cut-off value of 2.77 (sensitivity = 84.6%, specificity = 89.7%, 95% CI = 0.86–0.97). Conclusions ESR and CRP seem not to be sensitive for the diagnosis of early PJI due to their persistently high levels after arthroplasty. The postoperative NLR at the suspected time may have a great ability to predict early PJI.